2006
DOI: 10.1212/01.wnl.0000204296.15607.37
|View full text |Cite
|
Sign up to set email alerts
|

Does the arousal system contribute to near death experience?

Abstract: The neurophysiologic basis of near death experience (NDE) is unknown. Clinical observations suggest that REM state intrusion contributes to NDE. Support for the hypothesis follows five lines of evidence: REM intrusion during wakefulness is a frequent normal occurrence, REM intrusion underlies other clinical conditions, NDE elements can be explained by REM intrusion, cardiorespiratory afferents evoke REM intrusion, and persons with an NDE may have an arousal system predisposing to REM intrusion. To investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(132 citation statements)
references
References 82 publications
8
122
0
2
Order By: Relevance
“…The resulting state (partial awareness combined with abnormal somatosensory and motor signals) has been proposed as a main pathomechanism for awareness during general anesthesia (Blacher, 1975;Moermann et al, 1993;Sandin et al, 2000;Spitellie et al, 2002) and might also account for OBEs in these circumstances (Bü nning and Blanke, 2005). Thus, disturbed somatosensory and sensorimotor signals from large parts of the body in (1) tetraplegia with severe somatosensory loss (as in our patient), (2) during general anesthesia (Moermann et al, 1993), and (3) during sleep paralysis (Nelson et al, 2006;Girard et al, 2007;Cheyne and Girard, 2009, this issue) seem to disturb integration of multisensory body-related information in personal space due to interference with brainstem, spinal cord and peripheral nervous system signalling information from the somatosensory and motor systems. As REM intrusions or sleep paralysis have been linked to damage or interference with brainstem mechanisms, the present observation suggests the implication of mechanisms in the cervical spinal cord.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The resulting state (partial awareness combined with abnormal somatosensory and motor signals) has been proposed as a main pathomechanism for awareness during general anesthesia (Blacher, 1975;Moermann et al, 1993;Sandin et al, 2000;Spitellie et al, 2002) and might also account for OBEs in these circumstances (Bü nning and Blanke, 2005). Thus, disturbed somatosensory and sensorimotor signals from large parts of the body in (1) tetraplegia with severe somatosensory loss (as in our patient), (2) during general anesthesia (Moermann et al, 1993), and (3) during sleep paralysis (Nelson et al, 2006;Girard et al, 2007;Cheyne and Girard, 2009, this issue) seem to disturb integration of multisensory body-related information in personal space due to interference with brainstem, spinal cord and peripheral nervous system signalling information from the somatosensory and motor systems. As REM intrusions or sleep paralysis have been linked to damage or interference with brainstem mechanisms, the present observation suggests the implication of mechanisms in the cervical spinal cord.…”
Section: Discussionmentioning
confidence: 59%
“…Accordingly, it has been hypothesised that generalized paralysis during REM-sleep dreams might be a precipitating factor of such OBEs (Bü nning and Blanke, 2005). The data of Girard et al (2007) also show that OBEs and autoscopic hallucinations are related to sleep paralysis and recent studies found that subjects with near death experiences that include OBEs more commonly have sleep paralysis (Nelson et al, 2006(Nelson et al, , 2007; see also Blanke and Dieguez, in press). More studies are needed to investigate the association between OBEs, dreaming, REM phase, and sleep paralysis in greater detail.…”
Section: Discussionmentioning
confidence: 70%
“…NDEs have also been associated speculatively with intrusion into waking consciousness of thought patterns typical of dream sleep [85]. However, NDEs typically occur under conditions that inhibit dream sleep, such as general anesthesia [86], and dream sleep is actually reduced in near-death experiencers [73].…”
Section: Physiological Explanationsmentioning
confidence: 99%
“…The American Psychiatric Association (2000) appeared to distinguish REM intrusion, that is, visual and auditory hallucinations and sleep paralysis, from cataplexy. However, Nelson, Mattingly, Lee, and Schmitt (2006) included cataplexy as a form of REM intrusion.…”
Section: Rem Intrusionmentioning
confidence: 99%